ANALISIS PROSEDUR PEMBERIAN KREDIT DAN PENAGIHAN PIUTANG DALAM MEMINIMALKAN PIUTANG TIDAK TERTAGIH PADA PT ANEKA TATA NIAGA - Sugianto, Julita; Natalia, Erni Yanti (SCIENTIA JOURNAL, 2021)
Every company needs to compete tightly and optimally in order to maintain the survival of its company. One of the actions that companies can take is to make sales on credit that generate accounts receivable to earn income. However, in general sales on credit carry the risk of bad debts. The company must be able to review the execution of sales properly as well as effective crediting and collection procedures for accounts receivable. The purpose of this study is to analyze the procedures for granting credit and collection of accounts receivable in minimizing uncollectible accounts. The method used in this study is a qualitative research method with observative data collection, interviews with parties related to the research, and documentation obtained from the company under study. The population in this study is PT Aneka Tata Niaga, and the sample of this study is data on uncollectible accounts from PT Aneka Tata Niaga. The result of this research is that the procedure for granting credit to PT Aneka Tata Niaga begins by filling in a new customer data form which will then be approved by the sales manager and director, the collection of accounts receivable at PT Aneka Tata Niaga is carried out by the accounts receivable admin section in preparing the invoices and receipts needed in collection to customers, uncollectible receivables at PT Aneka Tata Niaga are caused by internal and external factors. The obstacle faced by PT Aneka Tata Niaga is having a simple manual-based accounts receivable control system in Microsoft Excel, a system planned by PT Aneka Tata Niaga in minimizing uncollectible accounts receivable is to establish a system in "GF Accounting".